Scales and properties of cold filaments in the Benguela upwelling system off Lüderitz. Issue 3 (24th March 2016) - Hösen, Elisabeth; Möller, Judith; Jochumsen, Kerstin; Quadfasel, Detlef
Abstract: The Benguela upwelling system is one of the four strongest upwelling systems in the world. Meso‐scale and submeso‐scale structures like eddies and filaments build up at the front between the cold upwelled water and the warm surface water offshore. From three and a half years of satellite data (MODIS) of sea surface temperature (SST) more than 450 filaments were identified and used for extensive statistics of the scales, the occurrence frequency and the location of filaments in the Lüderitz upwelling cell and its vicinity. In situ data of SST, sea surface salinity and profiles of temperature, salinity and velocity collected during six cruises between September 2011 and February 2014 provide information on the properties of filaments and on their vertical structure. The occurrence of the filaments shows a maximum in austral summer and a minimum in September similar to the seasonal intensity of the upwelling. Within the Lüderitz cell, filaments have a meridional extent between 5 km and 80 km, an offshore extent between 20 km and more than 500 km and a vertical extent between 70 m and 180 m. The temperature within the filaments is 0.25 – 2.5°C lower than the ambient temperature and their salinity is up to 0.6 lower than the ambient salinity. Within the filaments westerly currents with velocities up to 30 cm/s were observed. Mean filament properties and occurrence result in an offshore volume transport of 3 Sv and a heat transport anomaly of −3 × 10 13 W. Key Points: Typical scales are determined from about 450 filaments using satellite data. Hydrographic and current properties are obtained from in situ measurements. Filaments contribute significantly to the exchange between the coastal region and the open ocean.